1996
DOI: 10.1161/01.res.79.6.1188
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer Stimulation Unmasks Latent Gene Transfer After Adenovirus-Mediated Gene Delivery Into Human Vascular Smooth Muscle Cells

Abstract: Recombinant adenoviral vectors are being used increasingly for gene transfer studies in mammalian cells and gene therapy protocols in humans. High adenoviral titers are often required for successful transduction of vascular smooth muscle cells (VSMCs), defined as uptake and detectable expression of the foreign gene, but the relative contributions of efficiency of viral uptake and control of transcription are poorly understood. To explore the extent to which a lack of detectable gene expression may be due to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…25 In addition, a published study from our laboratory documented promoter-dependent variation in the tissue expression of a reporter transgene following injection of adenovirus into the early stage mouse embryo in culture (7.5-9 days); 26 CMV promoter control resulted in primarily endothelial expression while RSV control resulted in preferential expression within the myocardium. Similarly, Woo et al 16 found that the expression pattern of ␤-gal under RSV promoter control resulted primarily in myocardial cell expression when adenovirus was injected at a single developmental timepoint (12.5 d.p.c.)…”
Section: Embryos (A) Hybridization With Control Sense Probe Reveamentioning
confidence: 99%
“…25 In addition, a published study from our laboratory documented promoter-dependent variation in the tissue expression of a reporter transgene following injection of adenovirus into the early stage mouse embryo in culture (7.5-9 days); 26 CMV promoter control resulted in primarily endothelial expression while RSV control resulted in preferential expression within the myocardium. Similarly, Woo et al 16 found that the expression pattern of ␤-gal under RSV promoter control resulted primarily in myocardial cell expression when adenovirus was injected at a single developmental timepoint (12.5 d.p.c.)…”
Section: Embryos (A) Hybridization With Control Sense Probe Reveamentioning
confidence: 99%
“…9 Stimulation of NF B and CREB response elements in the CMV-IEP were required to unmask ␤-galactosidase expression after low multiplicity infection, however, high multiplicity infection led to effective transduction without enhancer stimulation. This raised the hypothesis that high multiplicity infection itself was able to modify the transcriptional environment to augment expression from the CMV-IEP.…”
Section: Introductionmentioning
confidence: 99%
“…However, pharmacological enhancement increased the proportion of SMC expressing transgene following gene transfer at MOI¼10 from 5 to 55%, suggesting, that in the absence of enhancer stimulation, 490% of copies of MIEhCMV entering SMC fail to express transgene. 4 Unfortunately, these methods of enhancement are not well suited to in vivo application. Furthermore, the ideal vector for vascular gene therapy should allow maximal transgene expression after a single dose without further physical or pharmacological manipulations.…”
Section: Discussionmentioning
confidence: 99%
“…After adenovirusmediated gene transfer at a multiplicity of infection (MOI) of 10, only a small proportion (E5%) of infected SMC expresses detectable levels of transgene when transcriptional regulation is governed by the MIEhCMV. 4 Other viral promoters such as the Rous Sarcoma Virus long terminal repeat promoter or Simian Virus 40 early promoter typically give rise to less transgene expression in SMC than MIEhCMV. 5 Transcriptional targeting employing SMC-specific promoters has successfully conferred cell-type specificity, 6 but the magnitude of transgene expression achieved using the SMC-specific SM22a promoter was less than that achieved using MIEhCMV.…”
Section: Introductionmentioning
confidence: 99%